(untitled) (Research, Society and Development, 2024)
Cardiorespiratory arrest (CRA) is a medical emergency with a high mortality rate, and its effective management is crucial for patient survival and recovery. This study aimed to review and describe nursing care in the emergency unit during and after CRA, based on a narrative literature review. Using data from scientific articles published between 2014 and 2023, the study emphasized the importance of early recognition of CRA signs, the proper execution of cardiopulmonary resuscitation (CPR) maneuvers, and post-CRA care management. The results highlighted that successful resuscitation is directly linked to the efficient performance of chest compressions, immediate defibrillation, and accurate administration of medications. Continuous monitoring and psychological support for family members are also essential for quality care. The study concludes that continuous training and the updating of CPR guidelines are indispensable for improving clinical outcomes and reducing the sequelae and mortality associated with CRA.